About RAMP- Research and Market Pathway - CGIAR Accelerate For Impact Platform (2025)
RAMP is an internal accelerator to equip Alliance/CGIAR scientists with the skills and support needed to translate scientific discoveries into market-viable solutions that create impact-at-scale. Discover more about the cohort of innovators.